Inorganic nitrate supplementation improves diastolic function in cancer survivors treated with anthracycline chemotherapy - Lovoy, Garrett M. (Kansas State University, 2018)
Background: Cancer survivors treated with anthracycline-based chemotherapy have a high risk of developing anthracycline-induced cardiotoxicities, including cardiac abnormalities, endothelial dysfunction, and dilated cardiomyopathy. Notably, the imbalance of decreased nitric oxide (NO) production and increased reactive oxygen species has been shown to cause significant damage to cardiac tissue and mitochondria. Therefore, the aim of the current investigation was to determine if an inorganic dietary nitrate (NO3-) supplementation period could restore normal cardiac function in cancer survivors with a history of anthracycline chemotherapy. Methods: Ten cancer survivors, 9 with breast cancer and 1 with lymphoma, completed the experiment. Standard and Tissue Doppler echocardiography were used to assess LV and carotid artery function during systole and diastole at rest. Results: There were no differences in ventricular-arterial coupling (p=0.10), arterial stiffness (p=0.38) or strain of the LV (p=0.49). However, NO₃- supplementation improved strain rate in early filling, early mitral septal wall annular velocity, and mitral A-wave velocity or late diastolic filling. Conclusion: Following NO₃- supplementation, cancer survivors with a history of anthracycline chemotherapy showed significant improvements in diastolic function compared to placebo treatments. These findings add support to the literature of the therapeutic benefits of inorganic dietary NO₃- supplementation on cardiovascular function in clinical populations.
Keywords: Anthracycline; Cancer; Echocardiography; Nitrate; Nitric Oxide